Influence of Temperature and Current Stressing on Cu‐Sn Intermetallic Compound Growth Characteristics of Lead‐Free Microbump. Issue 4 (15th February 2023) - Fu, Zhiwei; Wei, Qinru; Guo, Xiaotong; Fu, Xing; Wang, Jian; Yang, Chao; Guo, Huaixin; Yang, Jia‐Yue
Abstract: A numerical analysis of the Cu flux on Cu/Sn/Cu is successfully used to establish kinetic models that are verified with reported data. Kinetic models are adopted to discuss the polarity effect of intermetallic compounds (IMCs) growth at different alloying stages. The models reveal that, before Sn solder is depleted during thermal aging, the net thermodiffusion Cu flux in Cu6 Sn5 is over three times larger than that in Cu3 Sn. While coupling with current stressing, the IMCs thickness increases from parabola‐like curves to a linear‐like relationship. The degree of influence decreases in the order of Cu6 Sn5 on anode, Cu6 Sn5 on cathode, Cu3 Sn on anode, and Cu3 Sn on cathode. Electromigration Cu flux in Sn is the critical factor that accelerates the anode's Cu6 Sn5 growth, and its influence on the growth rate over 1000 times that on the anode's Cu3 Sn. After Sn solder is depleted, Cu6 Sn5 gradually converts into Cu3 Sn, and its thickness is linearly decreases with square root of annealing time. When coupling with a current density of 1.0 × 10 5 A cm −2, the thickness ratio of Cu3 Sn/Cu6 Sn5 reduces from 1:2 to 1:6. Remarkably, irrespective of whether current exists or not, the depletion of Cu6 Sn5 always takes much longer than that of Sn solder. Abstract : Through the quantitative analysis of Cu flux, kinetic models are established to analyze the polarity effect of Cu6 Sn5 and Cu3 Sn growth. The evolution mechanism between Cu6 Sn5 and Cu3 Sn is studied at different alloying stages and has been successfully applied to predict the conversion time.